Freedom, Transcendence and Identity: Essays in memory of Kalidas Bhattacharya - Chethimattam, John B (Journal of Dharma, 1992)
Freedom, Transcendence and Identity, Essays in memory of Kalidas Bhattacharya, (ed.) Pradip Kumar Sengupta, Delhi, Motilal Banarsidass, 1988, pp. viii+222. Rs. 1 35.